Pengaruh Pelatihan Kerja dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT Maxley BSD Tangerang - Supratman, Putri Alenisa; Eka, Priehadi Dhasa (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the effect of job training and physical work environment on employee performance at PT Maxley BSD Tangerang during the 2024–2025 period. The research employed a quantitative approach with a descriptive design. The sample consisted of all 50 employees using a saturated sampling technique. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²) with the assistance of SPSS version 27. The results show that partially, job training has no significant effect on employee performance with a significance value of 0.960 > 0.05. In contrast, the physical work environment has a positive and significant effect on employee performance with a significance value of 0.000 < 0.05. Simultaneously, job training and the physical work environment significantly affect employee performance with a significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.612 indicates that both variables explain 61.2% of the variation in employee performance, while the remaining 38.8% is influenced by other factors outside this study.